TEACHING ENGLISH VOCABULARY BY USING ENGLISH SONG - Choirunnisa, Any; Regina, Regina; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purposes of this research are to investigate whether or not the use of English song  to improve students’ vocabulary achievement in teaching English vocabulary  and to find out the effect size of the improvement of students’ vocabulary achievement after being taught using English song to the eighth grade students of SMP Muhammadiyah 2 Pontianak. The sample of this research was 34 students in class VIII A. The data of study was derived from pre test and post test. The technique of data collection is measurement technique and the tool of data collection is a test in form of fill in the blanks test. The research findings show that the mean score of pre-test is 75.85while the mean score of post-test is 85.76. It means that English song improves the students’ vocabulary achievement. Furthermore, the effect size of the significant improvement of the treatment was 0.8. It is categorized as highly effective since it is higher than 0.5. The teacher might put some appropriate variations in applying the strategy considering the situation and condition found in the classroom. Keywords: Teaching English, Vocabulary, English Song